Механизм образования наноактивных комплексов Rh-Pd катализатора очистки CO₂ в производстве карбамида - Казаков, В. В. (НТУ "ХПИ", 2015)
Представлены основные результаты исследований процесса регенерации отработанного катализатора РПК-1 под воздействием электромагнитных и акустических полей. Показано, что при обработке катализатора монохроматическим пучком частиц сонаров и поляритонов, происходит образование однородных центров нанокатализа и параллельно аннигиляция каталитических центров, ответственных за сторонние химические реакции. Приведены дифференциальные уравнения, описывающие механизм изменения концентраций основных продуктов реакции.

The main results of research on the regeneration of spent catalyst RPK-1 under the influence of electromagnetic and acoustic fields. It is shown that the treatment of the catalyst particles monochromatic beam sonar and polaritons, the formation of homogeneous centers nanokataliza and parallel to the annihilation of the catalytic sites are responsible for third-party chemical reactions. Differential equations that describe the mechanism for changing concentrations of the major products of the reaction. It is concluded that the spatial and temporal distribution of radical (H•, OH•) and molecular products (H₂, H₂O₂) produced when exposed to water electromagnetic and acoustic waves. Analysis of physical, chemical and technical characteristics of the catalyst shown that electromagnetic and acoustic fields generated nanostructured catalytic contact with a physico-chemical characteristics, previously not observed in similar catalysts.
The mechanism of nano activity complexes formation Rh-Pd catalysts for cleaning CO₂ in production of carbamid
Keywords: синтез карбамида; газ углекислый; примесь горючая; регенерация катализатора; поле акустическое; поле электромагнитное; synthesis of carbamid; carbon dioxide; combustible impurities; catalyst regeneration; acoustic field; electromagnetic field; nanostructured catalyst contact